Penerapan Algoritma Genetika Untuk Penjadwalan Mata Pelajaran Di SMK Negeri 1 Kota Tambolaka - Padaka, Emirensiana; Tetik, Yulius Nahak; Ledi, Dian Fransiska (CV. ITTC INDONESIA, 2023)
consider other things such as avoiding the same or repeated schedules in one day, the number of teaching staff involved, and practicum subjects which in their implementation require a laboratory. The subject scheduling process at SMK Negeri 1 Tambolaka City is still carried out manually by Deputy Head 1 for the curriculum field, who currently uses Microsoft Excel software, which has the potential for errors and often requires correction before the schedule is implemented. Because the subject scheduling process is very important, a solution is needed in making subject schedules. Therefore, this research aims to optimize course schedules by applying a genetic algorithm to the course scheduling application. In this research, the process of preparing rosters for applied subjects was carried out at school using a web-based genetic algorithm method so that schedule collisions did not occur and the process was more optimal. In the experiment, the results of this subject scheduling application system consisted of several forms and menus, including a login form, department data menu, subject data, class data, teachers, hour ranges, special schedules, and the scheduling menu. Creating a teacher's teaching schedule using a genetic algorithm can produce a schedule automatically and systematically, thereby displaying the schedule for the day and time of each teacher's teaching schedule. The application of genetic algorithms in scheduling teacher teaching at SMK Negeri 1 Tambolaka City is a very optimal solution for scheduling, so that the possibility of similarities in the same teacher's teaching time and hours is very small.